Tunable terahertz all-dielectric linear-to-circular polarization conversion metasurface - Ju, Xiacao; Wang, Weiguang; Liu, Bingchao; Hou, Yanzhao; Wen, Huashun; Yang, Daquan (Oficyna Wydawnicza Politechniki Wrocławskiej, 2022)
Terahertz (THz) linear-to-circular (LTC) polarization conversion plays a crucial role in imaging and 6G wireless communication. This paper will give an account of a thermally tunable THz LTC polarization converter by using the active all-dielectric metasurface. It consists of zirconium oxide (ZrO2) microsphere resonators, active strontium titanate (STO) cladding, and flexible polyimide substrate. Through numerical simulation, the amplitude of the ellipticity of the proposed polarization converter at 0.265 THz is –1, indicating that perfect right-hand circular polarization (RHCP) wave is achieved. Meanwhile, the amplitude of the ellipticity is less than –0.8 between 0.247 and 0.278 THz (relative bandwidth is 12%). In addition, with the temperature changes of 180 K (from 200 to 380 K), the operating frequency of the converter can be tuned from 0.220 to 0.291 THz, a sensitivity about 39 GHz/100 K is achieved. Besides, the modulation depth of the ellipticity amplitude can achieve 92% at 0.220 THz, which demonstrates that the converter can output terahertz wave with different polarization states, and the device can be fabricated on a large scale. These perfect conversion performances show that the converter has potential applications in high-speed communication and imaging.
Optica Applicata, Vol. 52, 2022, nr 4, s. 551-563
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; terahertz waves; dynamically tunable; strontium titanate; polarization conversion; all-dielectric metasurface